Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1002/jnr.490180310
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord interneuron degenerative atrophy caused by peripheral nerve lesions is prevented by serotonin depletion

Abstract: Peripheral nerve section causes a degenerative atrophy of substance P sensory input and of met-enkephalin interneurons in the dorsal horn of the spinal cord. Radioimmunoassay of both peptides indicates that the decrease in peptide levels ranges from 30 to 50%, that it occurs several days after lesioning, and that it is simultaneous for the two peptides. Quantitative immunocytochemistry performed by computer-assisted analysis of met-enkephalin-positive boutons shows that following sciatic nerve lesions there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 15 publications
(4 reference statements)
2
19
0
Order By: Relevance
“…The homogenate was split into two aliquots, one for 5-hydroxyindoles (5-HT and 5-HIAA) and the other for catecholamines (NA and DA) quantification. The aliquot for 5-HT and 5-HIAA assay was centrifuged at 40,OOOg for 15 min and the resulting supernatant diirectly injected into the HPLC apparatus (Di Giulio et al, 1987). Catecholamine assay required an intermediate purification step by adsorption into allumina.…”
Section: Monoamine and Peptide Assaysmentioning
confidence: 99%
“…The homogenate was split into two aliquots, one for 5-hydroxyindoles (5-HT and 5-HIAA) and the other for catecholamines (NA and DA) quantification. The aliquot for 5-HT and 5-HIAA assay was centrifuged at 40,OOOg for 15 min and the resulting supernatant diirectly injected into the HPLC apparatus (Di Giulio et al, 1987). Catecholamine assay required an intermediate purification step by adsorption into allumina.…”
Section: Monoamine and Peptide Assaysmentioning
confidence: 99%
“…Animals were kept under standard conditioned and killed at the appropriate time. Brain and spinal cord were quickly dissected out, frozen in liquid nitrogen and kept at -80°C until assay (Di Giulio et al, 1987, 1989aGorio et al, 1993Gorio et al, , 1996. An approximate equal number of female and male animals were studied in each group.…”
Section: Methodsmentioning
confidence: 99%
“…previously published procedures (Di Giulio et al, 1987, 1989. Briefly, 21 days after sciatic nerve resection animals were anesthetized with 30 mg/kg pentobarbital i.p.…”
Section: Neuroprotection and Glycosaminoglycans 573mentioning
confidence: 99%
“…Also substantia gelatinosa interneurons undergo atrophy following sciatic nerve lesion, and it has been shown that in the dorsal horn there is loss of metenkephalin (Met-Enk) and the relative neurons undergo atrophy (Di Giulio et al, 1985, 1989. The MetEnk changes are regulated by the descending serotoninergic pathways and activated b y the sciatic nerve lesion (Di Giulio et al, 1987). In addlition there is a 40% loss of opiate receptors (Ninkovic et al, 1981).…”
Section: Introductionmentioning
confidence: 98%